Content Analysis of Police Images On Instagram Followers Of Sahabat Polisi Indonesia - Sabena, Sabena (Reputasi : Jurnal Public Relations, 2025)
This book is a complete guide that helps readers learn to speak in public confidently and effectively. This book combines Behaviorism Theory, covering all behavior, starting from counteraction or response to a stimulus or stimuli with practice and offers practical suggestions for improving public speaking skills. Readers will be guided through a systematic learning process aimed at improving their confidence and public speaking skills, from mental preparation to techniques on how to regulate voice and body movements. In addition, this book emphasizes the importance of how to understand your audience, create structure during an effective presentation, and how to overcome common problems such as nervousness and uncertainty when speaking . The aim of writing this book is to be a valuable resource for anyone who wants to improve their public speaking skills and become an expert in conveying ideas and influencing others. Keywords: Content Analysis, Police, Instagram, Online Community, Public Opinion.